Academic Commitments to Sustainability at PSU - Triplett, Jim (Kansas State University, 2012)
This poster will detail the Bachelor of Integrated Studies in Sustainability, Society and Resource Management at Pittsburg State University. In addition, other programs that have specific commitments to sustainability will be highlighted.
Keywords: Sustainability; Bachelors degree